On the seasonal freshwater stratification in the proximity of fast‐flowing tidewater outlet glaciers in a sub‐Arctic sill fjord. Issue 3 (20th March 2013) - Mortensen, J.; Bendtsen, J.; Motyka, R. J.; Lennert, K.; Truffer, M.; Fahnestock, M.; Rysgaard, S.
Abstract: [1] The Greenland Ice Sheet releases large amounts of freshwater into the fjords around Greenland and many fjords are in direct contact with the ice sheet through tidewater outlet glaciers. Here we present the first seasonal hydrographic observations from the inner part of a sub‐Arctic fjord, relatively close to and within 4–50 km of a fast‐flowing tidewater outlet glacier. This region is characterized by a dense glacial and sea ice cover. Freshwater from runoff, subglacial freshwater (SgFW) discharge, glacial, and sea ice melt are observed above 50–90 m depth. During summer, SgFW and subsurface glacial melt mixed with ambient water are observed as a layered structure in the temperature profiles below the low‐saline summer surface layer (<7 m). During winter, the upper water column is characterized by stepwise halo‐ and thermoclines formed by mixing between deeper layers and the surface layer influenced by ice melt. The warm ( T  > 1°C) intermediate water mass is a significant subsurface heat source for ice melt. We analyze the temperature and salinity profiles observed in late summer with a thermodynamic mixing model and determine the total freshwater content in the layer below the summer surface layer to be between 5% and 11%. The total freshwater contribution in this layer from melted glacial ice was estimated to be 1–2%, while the corresponding SgFW was estimated to be 3–10%. The winter measurements in the subsurface halocline layer showed a total freshwater content of about 1% and no significant contribution from SgFW. Key Points: First seasonal analysis of freshwater distribution close to a tidewater glacier Fraction model of glacial ice melt and subglacial freshwater discharge Major implication for understanding the glacier‐fjord‐interaction